Design of Airborne Weapon Combat System and Key Technologies Analysis - Guo Chao, Zhao Guohong, Pan Hui (Hangkong bingqi)
In response to the evolution of air combat system, new target threat and complex operational environment, this paper introduces the design of airborne weapon combat system and key technologies analysis. Firstly, the opportunities and challenges for airborne weapon combat system are analyzed from the aspects of the user’s attention to the importance of the weapon systematic development and the relevant enterprise’s active layout of the weapon systema-tic development. Subsequently, this paper introduces the airborne weapon combat system design process from the aspects of combat concept design, system architecture modeling, combat style design, combat simulation and combat effectiveness evaluation. Finally, it analyzes the key technologies of airborne weapon combat system such as capability requirements, system architecture, deduction simulation, effectiveness evaluation.